Realizing an Environmentally Friendly and Educational School through the KKN Program at SDN Sumberjati: Mewujudkan Sekolah Ramah Lingkungan dan Edukatif melalui Program KKN di SDN Sumberjati - Arvia, Hilda Azizah; Akhfidhini, Brillianty; Albab, Rafa Azka Dzil; Agustin, Selly; Anwar, Najih (International Consortium of Education and Culture Research Studies, 2025)
General Background: Real labor lectures (KKN) are community service programs designed to bridge academic knowledge with practical societal contributions. Specific Background: At SDN Sumberjati, the KKN initiative aims to foster an engaging and educational school environment through student-led interventions. Knowledge Gap: Despite the growing emphasis on community-based education, limited documentation exists on integrated KKN programs that simultaneously address academic enhancement, environmental awareness, and sustainability in primary education settings. Aims: This study aims to explore the implementation and outcomes of a multidimensional KKN program at Sumberjati Elementary School, focusing on educational support and environmental initiatives. Results: The program included tutoring to improve academic comprehension, the creation of waste bins from recycled materials to promote environmental responsibility, hydroponic plant development to introduce sustainable agriculture, and direct classroom engagement to support the learning process. These initiatives collectively enriched the students' educational experiences and heightened their environmental consciousness. Novelty: The integration of environmental and educational components within a single KKN program presents a holistic model of university-community collaboration, emphasizing both cognitive development and ecological literacy among young learners. Implications: The findings suggest that such multidisciplinary KKN programs can significantly enhance the learning environment and instill sustainable values in primary school students, while simultaneously serving as a platform for university students to apply theoretical knowledge in real-world contexts. Keywords: KKN, SDN Sumberjati, Environmental Education, Tutoring Program, Sustainable Practices Highlights: Tutoring and hydroponics improved academic and sustainability awareness. Recycled waste bins fostered eco-friendly habits in students. University-community synergy enabled real-world knowledge application.